The effects of acute exercise on driving and executive functions in healthy older adults. Issue 1 (2nd January 2022) - Lebeau, Jean-Charles; Mason, Justin; Roque, Nelson; Tenenbaum, Gershon
ABSTRACT: The benefits of exercise on cognitive functioning in older adults are well recognised. One limitation of the current literature is that researchers have almost exclusively relied on well-controlled laboratory tasks to assess cognition. Moreover, the effects of a single bout of aerobic exercise in older adults have received limited attention. The proposed study addresses these limitations by assessing the effects of a single bout of exercise on a more ecologically valid task – driving. Seventy-one participants ( M age = 66.39 ± 4.70 years) were randomly allocated to 20 min cycling at moderate intensity or sitting and watching driving videos. Participants were then tested on their driving performance using a driving simulator. Driving performance was measured with three different scenarios assessing decision making, driving errors, reaction time, and attention. On a subsequent session, all participants were tested on executive functioning before and after a fitness test. Non-significant effects of exercise were observed on driving performance. However, participants performed better on the Trail Making Test (Cohen's d = 0.25) and Stroop test ( d = 0.50) after the fitness test compared to their baseline. These results suggest that post-exercise cognitive improvements do not transfer to improved driving performance among healthy older adults. This study also highlights the importance of assessing expectations as a possible moderator of the effects of acute exercise on activities of daily living. Future studies must examine other relevant ecologically valid tasks and ensure similar expectations between experimental and control groups to further advance the knowledge base in the field.